Electrical Equivalent Circuit Model Prediction of High-Entropy Alloy Behavior in Aggressive Media - Cabrera-Peña, Jose; Brito-Garcia, Santiago Jose; Mirza-Rosca, Julia Claudia; Callico, Gustavo M. (MDPI AG, 2023)
Due to the optimistic outcomes of the research on high-entropy alloys, new designs of these alloys are being encouraged. We studied the high-entropy CoCrFeMoNi alloy and the CoCrFeMoNi alloy doped with Zr. In order to choose the best electrical equivalent circuit for the prediction of the behavior of these high-entropy alloys at various potentials in artificial seawater, electrochemical impedance spectroscopy (EIS) measurements were conducted on samples with and without Zr-doped CoCrFeMoNi. At various potential levels, the impedance spectra were measured between −1.0 and +0.8 V vs. SCE. The study consists of a preliminary section with microstructure by metallography, open-circuit potential, and linear polarization curves by direct-current tests followed by visual analysis of the impedance spectra, and, finally, the selection of an equivalent electrical circuit model to fit the experimental data. By leveraging the advantages of EIS analysis, the information is essential for materials development, corrosion-mitigation strategies, and the successful implementation of these alloys in practical applications. It is important to note that selecting an equivalent circuit is often an iterative and subjective process, as it involves a balance between model complexity and the ability to accurately represent the system’s behavior.
The authors thank Ionelia Voiculescu y Victor Geanta of ERAMET Laboratory of the Politehnica University of Bucharest, Romania, for providing the high-entropy alloys and for their assistance and comments regarding this work.
Keywords: EIS; equivalent circuit; Zr-doped; high-entropy alloys